Kualitas Pelayanan Publik Administrasi Kependudukan dalam Kerangka Undang-Undang Pelayanan Publik di Kantor Camat Medan Denai Kota Medan - Iqbal Al Ahmid; Julia Ivanna (CV Rewang Rencang, 2025)
This study aims to determine the quality of public services in population administration at the Medan Denai Sub-District Office in Medan City. The background to this study is the discovery of several problems in public services related to population administration. First, there is the issue of employee discipline. Second, the performance of officers is still weak. Third, there is a lack of empathy from officers. Fourth, there are issues with service time guarantees. This study is descriptive in nature and uses qualitative methods. The subjects of the study are the Head of the General Affairs Division, the Head of the Governance Division, two governance officers, and six members of the public who require services. Data collection techniques include interviews, observation, and documentation. The results of the study show that the community is satisfied with the services, although there are still complaints regarding service completion. Therefore, it can be said that the quality of civil registration services at the Medan Denai Sub-District Office is quite good, especially in terms of physical aspects, clarity of information, and the professional attitude of the officers.